European initiatives for a competitive economy in a globalised world- Entrepreneurial innovation as a pivotal stake - SIRBU Olesea; CRUDU Rodica; IGNATOV Augustin (Eastern European Journal of Regional Studies)
The global economic crisis has revealed the main weaknesses of the European Union’s economy, including slow decision making, over-regulation and excessive bureaucratisation, lack of economic cohesion among the various nations of the EU, uneven competitive readiness and poor economic performance & development. Less flexible and more regulated, the European Union’s entrepreneurial environment is undermined by excessive governmental intervention justified by “soziale Marktwirtschaft” or the social market economic principles. The main stake of the European Union and member countries’ decision making factors and elites relies on stimulating entrepreneurial and public innovation as to raise the level of economic competitiveness. In such a way, it is possible to keep the present standards of living imposed by the principles of social market economy, and report at the same time competitiveness of more liberal-capitalistic economies. Taking into account these circumstances, the present research has established the goal to identify to which extent the initiatives promoted by the European Union in the area of innovation and entrepreneurship proved to have a beneficial effect upon community’s economic competitiveness taking into account the modern day economic challenges. As a result, there have been formulated two main hypotheses and namely, H1, which states that entrepreneurial innovation could not be compensated with public driven innovation policies and, H0, identifying the vice-versa and namely that governmental supported innovation can offset entrepreneurial innovation.